1993
DOI: 10.1002/cyto.990140606
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin study demonstrating the non‐linearity of fluorometry useful for calculating genomic base composition

Abstract: A novel procedure for calculating basepair frequencies in whole genomes is reported. This has been developed during a study of the role of heterochromatin in microevolution. Closely related species of the Crepis praemorsa complex have similar karyotypes but for their heterochromatin. The changes in relative AT frequency between species have been attributed to heterochromatin sequences by in situ banding of chromosomes with two base-specific fluorochromes. The absolute genome size of species, measured by cytofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 28 publications
4
77
0
Order By: Relevance
“…The base sequence of Pseudomonas aeruginosa was downloaded from the website of the Pseudomonas Genome Project http://www.pseudomonas.com/, all remaining sequences from the website of The Institute of Genomic Research (TIGR) http://www.tigr.org/ n DAPI ϭ n HO ⅐ ln͑DF_DAPI͒/ln͑DF_HO͒ (11) which follows from eq. (10) in Godelle et al (9).…”
Section: Comparison Among Dapi and Homentioning
confidence: 94%
See 2 more Smart Citations
“…The base sequence of Pseudomonas aeruginosa was downloaded from the website of the Pseudomonas Genome Project http://www.pseudomonas.com/, all remaining sequences from the website of The Institute of Genomic Research (TIGR) http://www.tigr.org/ n DAPI ϭ n HO ⅐ ln͑DF_DAPI͒/ln͑DF_HO͒ (11) which follows from eq. (10) in Godelle et al (9).…”
Section: Comparison Among Dapi and Homentioning
confidence: 94%
“…Doležel et al (6) showed that base-specific fluorescence is not proportional to the base content, but rather follows a curvilinear relation. Provided that the bases in the genome are distributed randomly, a formula is given for the relation between base frequency and fluorescence intensity (8,9). It is based on the condition that only a certain number, n, of consecutive bases of the same type (AT or GC) is able to bind a dye molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Angiosperms, haploid genome size varies from less than one picogram (pg) (Arabidopsis thaliana: 0.15 pg) [7] to more than 100 pg (Fritillaria assyriaca: 127 pg) [18]. Among techniques used for genome studies, flow cytometry is extremely rapid and convenient: it allows accurate determinations of nuclear DNA content [13] and of AT/GC base composition in a genome [15]. Favre and Brown [ 12] developed a fast and simple flow cytometry protocol for [14] with 0.5 % Triton X-100 and sodium metabisulfite (10 mM) as an antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate analysis of plant genome sizes also requires that the method of fluorochromatic staining be insensitive to basepair composition and/or the state of chromatin compaction. ISAC member Spencer Brown at Gif-sur-Yvette did pioneering work in this area (33,34).…”
Section: Flow Analysis Of the Plant Cell Cyclementioning
confidence: 99%